2015
DOI: 10.1099/vir.0.071084-0
|View full text |Cite
|
Sign up to set email alerts
|

Viral and cellular subnuclear structures in human cytomegalovirus-infected cells

Abstract: In human cytomegalovirus (HCMV)-infected cells, a dramatic remodelling of the nuclear architecture is linked to the creation, utilization and manipulation of subnuclear structures. This review outlines the involvement of several viral and cellular subnuclear structures in areas of HCMV replication and virus-host interaction that include viral transcription, viral DNA synthesis and the production of DNA-filled viral capsids. The structures discussed include those that promote or impede HCMV replication (such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 121 publications
0
19
0
2
Order By: Relevance
“…Indeed, it is possible that the upper limit of VRC number is restricted by availability of sites viable for the initiation and growth of VRCs. Interestingly, cellular chromatin is excluded from the VRCs of many DNA viruses, including HSV-1, CMV, and HAdV [11,12,14,15]. This raises the possibility that cellular chromatin must be manipulated to make space for VRC growth.…”
Section: What Dictates the Number Of Replication Compartments That Fomentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, it is possible that the upper limit of VRC number is restricted by availability of sites viable for the initiation and growth of VRCs. Interestingly, cellular chromatin is excluded from the VRCs of many DNA viruses, including HSV-1, CMV, and HAdV [11,12,14,15]. This raises the possibility that cellular chromatin must be manipulated to make space for VRC growth.…”
Section: What Dictates the Number Of Replication Compartments That Fomentioning
confidence: 99%
“…In many cases, the accumulation of these viral proteins throughout the nucleoplasm can be detected prior to the formation of VRCs [16,68,85], suggesting that their formation is concentration dependent, which is another feature of LLPS [87][88][89][90]. HSV-1, CMV, PRV, and HAdV VRCs also coalesce as infection progresses and they grow, fusing together in a liquid-like manner [14,15,61,62,65,69,95,[102][103][104]. However, it was recently demonstrated that HSV-1 VRCs are not disrupted by treatment with 1,6-hexanediol, which is a feature of many other cellular BMCs.…”
Section: Biophysical Processes In Replication Compartment Formationmentioning
confidence: 99%
See 2 more Smart Citations
“…Assembled capsids are then packaged with DNA before they translocate from the nucleus to the cytoplasm in a process called nuclear egress. To facilitate these steps, herpesviruses impart profound changes to host nuclear architecture, including the formation and expansion of RCs, partitioning of host chromatin, and disruption of the nuclear lamina (1). …”
Section: Introductionmentioning
confidence: 99%